Molecular phylogeny and diversity of Laburnicola (Didymosphaeriaceae): a new species from Uzbekistan - Htet, Zin Hnin; Mapook, Ausana; Gafforov, Yusufjon; Chethana, K.w. Thilini; Lumyong, Saisamorn; Hyde, Kevin D. (Phytotaxa, 2021)
Laburnicola is a genus in Didymosphaeriaceae that includes saprobic and endophytic fungal taxa. The current study conducted in the subalpine region of Uzbekistan discovered a new species on a dead stem of a wild rose plant. Maximum likelihood and Bayesian analyses of combined LSU, SSU, ITS, and TEF 1-ɑ dataset confirmed the new species’ taxonomic position in Laburnicola. Our new species, Laburnicola zaaminensis (TASM 6152), was clustered with L. dactylidis (MFLUCC 16-0285) with strong bootstrap support. A detailed description together with illustrations are provided for Laburnicola zaaminensis. Furthermore, an annotated species list, a distribution map, and a taxonomic key for Laburnicola species are provided. This is the first record of Laburnicola from Central Asia.